Ethics and Law for the Use and Development of Artificial Intelligence Technology - H. Yusep Mulyana (East Asian Journal of Multidisciplinary Research, 2023)
The development and use of Artificial Intelligence is growing exponentially, resulting in various implications in multi-sectors such as misuse of personal data, assessments prone to bias, uncontrolled automation, etc.) There is a legal vacuum (absence of law) in the use of Artificial Intelligence, so ethical principles of use are needed as a basis for developing a legal framework for Artificial Intelligence in the form of international conventions (law making treaties). Ethics and Law for the Use and Development of Artificial Intelligence Technology is that the use of AI can be an alternative and new breakthrough as an effort to prevent and minimize violations of ethical codes such as by public auditors. In the audit process, AI is designed to collect and determine data dynamically and then process the data to detect fraud in a relatively shorter time and with a higher level of accuracy than auditors in general. However, in the audit process carried out by AI, if viewed from the law enforcement factor, it cannot be said to be a legal subject because the requirements for law enforcement factors, namely facilities and facilities, have not been fulfilled.